Application Of Social Cognitive Theory And Islamic Theory Of Consumer Behavior In Accessing Muslim Behavior Toward Halal Nutraceuticals - Siti Nurunnajwa Shamsudin; Elistina Abu Bakar and Syuhaily Osman; Nuradli Ridzwan Shah Mohd Dali (Emerald Publishing Limited, 2024)
Indexed by WOS/Scopus/ERA